Impact of Ramadan Intermittent Fasting on the Heart Rate Variability and Cardiovascular Parameters of Patients with Controlled Hypertension - Sabah Hammoud; Iman Saad; Rita Karam; Fayez Abou Jaoude; Bart J. F. van den Bemt; Mazen Kurdi (Journal of Nutrition and Metabolism)
Background. Conflicting results are reported on the effect of Ramadan fasting on the cardiovascular health of patients with hypertension, a highly prevalent cardiovascular disease risk factor. This research aimed to evaluate the impact of fasting on cardiac health and heart rate variability (as a measure of cardiac stress) of hypertensive patients. Methods. Patients with controlled hypertension were followed in a prospective cohort during and after Ramadan. Lipid panel and blood glucose were measured at the end of each phase. Blood pressure and heart rate variability were monitored in the morning, afternoon, and evening of each follow-up day. Results. The study included 58 subjects (mean age: 54 ± 11.5 years, 52% male). Fasting did not affect body composition, lipid panel parameters, and blood pressure of hypertensive subjects; males only presented lower body weight and hip circumference during Ramadan. Blood glucose was significantly higher during Ramadan. Fasting significantly increased HRV during the afternoon period. Conclusions. Ramadan intermittent fasting reduces cardiac stress among hypertensive patients controlled by and adherent to hypertensive medication, without affecting their hypertensive state.